Disentangling climate-driven and vegetation-mediated impacts on water resources in the upper Yellow River Basin - Zhi Liang; Ruochen Sun; Qingyun Duan; Da Xu (Journal of Hydrology, 2026)

SWAT-UQ: A platform for uncertainty analysis, calibration and optimization of SWAT models - Mengtian Wu; Meihong Wu; Ruochen Sun; Xuan Huang; Shuo Yan; Jianjun Han; Qingyun Duan (Environmental Modelling & Software, 2026)

Integrated multi-dimensional framework for water conservation capacity evaluation and attribution in the Yellow River water conservation area - Da Xu; Ruochen Sun; Qingyun Duan; Zhi Liang; Xuejia Wang; Yan Ma (Journal of Hydrology, 2026)

The impact of green space environments on college students’ mental health at multiple spatial scales in Chinese universities: An empirical study based on a multilevel mediation model - Zhenhua Zheng; Yilin Jin; Wanting Liu; Ruochen Yin; Baitong Song; Jiajia Liu; Ning Sun; Hong Chen (Applied Geography, 2026)

An exergy-guided thermodynamic framework for the optimization of electro-membrane-based coupled process - Ruochen Shen; Yawei Du; Lurong Wang; Mengmeng Sun; Tianyi Chen; Shizhao Wang; Jingtao Bi; Wenhao Li; Jianlu Liu; Yingying Zhao (Water Research, 2026)

A co-support strategy to stabilize calcium-based carbon capture - Xingyue Ma; Tangfei Zhu; Wanlin Wang; Xiaobo Zhu; Ruochen Ning; Yongqi Sun (Journal of Environmental Chemical Engineering, 2025)

Interfacial engineering regulated Sm(CoXMn1-X)2O5 catalysts for highly efficient degradation of hexachlorobutadiene - Ruochen Wang; Shan Li; Guijin Su; Jia Duo; Liang Pei; Bohua Sun; Jing Meng; Bin Shi; Qianqian Li (Journal of Environmental Chemical Engineering, 2025)

Advancements in gas-liquid separation based on membrane contactors: Critical factors enhancing separation efficiency - Helin Wang; Tao Zhang; Ruochen An; Lin Sun; Xiaohui Weng; Zhiyong Chang (Process Safety and Environmental Protection, 2025)

Enhanced long-term carbon capture cycles of calcium oxide-based sorbents by regulating alumina sources - Xingyue Ma; Tangfei Zhu; Wanlin Wang; Xiaobo Zhu; Ruochen Ning; Yongqi Sun (Journal of Environmental Chemical Engineering, 2025)

A dual deep learning approach for winter temperature prediction in solar greenhouses in Northern China - Jingxin Yu; Jinpeng Zhao; Congcong Sun; Ruochen Zhang; Wengang Zheng; Linlin Xu; Xiaoming Wei (Computers and Electronics in Agriculture, 2025)

Surrogate modelling-based multi-objective optimization for best management practices of nonpoint source pollution - Aoyun Long; Ruochen Sun; Xiyezi Mao; Qingyun Duan; Mengtian Wu (Water Research, 2025)

Novel three-stage microalgal cultivation system for lipid production utilizing nutrients derived from refinery waste - Ruochen Wang; Wei Zhu; JiPeng Sun; Chi Zhang; Hongliang Dai; Tiantian Qu (Bioresource Technology, 2024)

Saline water treatment coupled with carbon dioxide capture by bipolar membrane electrodialysis in a continuous feed-bleed mode: The effect of proton leakage - Tianyi Chen; Ruochen Shen; Hongshuo Sun; Jingtao Bi; Mengmeng Sun; Shizhao Wang; Xiaofu Guo; Wenhao Li; Jianlu Liu; Yingying Zhao (Chemical Engineering Journal, 2024)

Bipolar membrane electrodialysis integrated with in-situ CO2 absorption for simulated seawater concentrate utilization, carbon storage and production of sodium carbonate - Jingtao Bi; Tianyi Chen; Yue Xie; Ruochen Shen; Bin Li; Mengmeng Sun; Xiaofu Guo; Yingying Zhao (Journal of Environmental Sciences, 2024)

Overlooked in-situ sulfur disproportionation fuels dissimilatory nitrate reduction to ammonium in sulfur-based system: Novel insight of nitrogen recovery - Bo Shao; Li Niu; Yuan-Guo Xie; Ruochen Zhang; Wei Wang; Xijun Xu; Jianxing Sun; Defeng Xing; Duu-Jong Lee; Nanqi Ren; Zheng-Shuang Hua; Chuan Chen (Water Research, 2024)

Occupational differences in the effects of retirement on hospitalizations for mental illness among female workers: Evidence from administrative data in China - Tianyu Wang; Ruochen Sun; Jody L. Sindelar; Xi Chen (Economics & Human Biology, 2024)

Design and control of a new omnidirectional levelling system for hilly crawler work machines - Yu Jiang; Zeyu Sun; Ruochen Wang; Renkai Ding; Qing Ye (Computers and Electronics in Agriculture, 2024)

An open online simulation strategy for hydrological ensemble forecasting - Yuanqing He; Min Chen; Yongning Wen; Qingyun Duan; Songshan Yue; Jiapeng Zhang; Wentao Li; Ruochen Sun; Zizhuo Zhang; Ruoyu Tao; Wei Tang; Guonian Lü (Environmental Modelling & Software, 2024)

One-step processing of waste dredged slurry into planting soil by targeted pretreatment and vacuum filtration - Silin Wu; Xiao Peng; Xiaohui Sun; Zijun Dong; Aizhao Zhou; Lei Zhang; Ruochen Wang (Journal of Environmental Management, 2024)

A surrogate modeling method for distributed land surface hydrological models based on deep learning - Ruochen Sun; Baoxiang Pan; Qingyun Duan (Journal of Hydrology, 2023)

Analytical method for quantifying performance of wicking geosynthetic stabilized roadway - Wuyu Zhang; Xiongyu Tang; Xiaohui Sun; Ruochen Yang; Guoqing Tong; Jun Guo (Geotextiles and Geomembranes, 2023)

Oceanospirillum sediminis sp. nov., Isolated From Coastal Sediment in the Yellow Sea - Huilin Zhao; Yue Tian; Xunke Sun; Qianwen Wu; Si Chen; Jiangfan Shan; Yu Zhong; Xinyu Chen; Xiaoxue Gao; Shengnan Liu; Ruochen Wang; Zongjun Du; et al. (Current Microbiology, 2022)

Maximum July–September temperatures derived from tree‐ring densities on the western Loess Plateau, China - Huiming Song; Ruochen Mei; Yu Liu; Daniel Nievergelt; Anne Verstege; Paolo Cherubini; Ruoshi Liu; Changfeng Sun; Qiang Li; Ling Chen; Xueli Zeng; Junqin Guo (International Journal of Climatology, 2021)
Tree‐ring densitometric studies conducted in semi‐arid regions are exceedingly rare. In this study, we evaluate a new maximum latewood density chronology from a collection of Picea purpurea trees growing in semi‐arid northwestern China for climatic reconstruction purposes. We find statistically significant correlations between annual maximum density variations and July–September maximum temperatures over the 1957–2014 calibration period. Using a linear model to transfer the density variations to temperature estimates, we then reconstruct maximum summer temperatures from 1840 to 2014. Statistical analyses and verification tests demonstrate that the resulting transfer function is both reliable and stable. The reconstructed temperature series shows strong inter‐annual and decadal variability. Several extremely cool and warm years are apparent on an inter‐annual scale, while three extended cool periods and a warm period are observed on a decadal scale. In addition, the reconstructed temperature series exhibits a pattern synchronous with that of the Indian monsoon index, as well as a moderate relationship to volcanic eruptions. This densitometric study reveals typical climatic variation characteristics and provides useful data for deepening our understanding of climate history in the semi‐arid regions of China.

Tree‐ring‐based precipitation reconstruction in the source region of Weihe River, northwest China since AD 1810 - Changfeng Sun; Yu Liu; Huiming Song; Ruochen Mei; Paramate Payomrat; Lu Wang; Ruoshi Liu (International Journal of Climatology, 2018)
A tree‐ring width chronology of Picea purpurea Mast from Mt. Shouyang in the source region of Weihe River (SWR), northwest China, was developed in this study. Correlation analysis showed that the precipitation from previous August to current July was the limiting climate factor of tree growth. Using a reliable and stable linear regression model, which explained 42.6% of the variance of the actual precipitation during the calibration period from 1958 to 2014, a 205‐year long precipitation series was reconstructed for the SWR. The dry years in the reconstruction were well supported by historical documents, and famous historical droughts were also recorded in the dry periods of a low‐frequency scale of the reconstructed precipitation. As demonstrated by the spatial correlation patterns, the reconstructed series compared well with other hydroclimate records for northwest China, indicating that it could represent large‐scale hydroclimate changes. The 2–8‐year interannual cycles and the interdecadal quasiperiods of 15.9 years and 18.6 years revealed that the precipitation in this region was probably affected by the El Niño‐Southern Oscillation and North Atlantic Oscillation. The dry/wet years corresponded well with the El Niño/La Niña events and the SWR commonly experienced droughts during the low periods of North Atlantic Oscillation.